COVID-19 vaccine hesitancy, chemical retraumatization, and madness. Issue 9 (13th October 2022) - Procknow, Greg
Abstract: Protecting the Section 7 autonomy rights of Canadian consumers/survivors/ex-patients and the mad (c/s/x/m), as enshrined in the Canadian Charter of Rights and Freedoms, with past experiences of enduring intrusive procedures forced upon them, to decline immunization against COVID-19 is a mad liberation issue, to which Mad Studies must not shut its eyes. To some c/s/x/m, vaccine mandates mirror traumatic moments from their psychiatric past, when they had their autonomy stripped, and their right to legal consent infringed upon by physicians of the mind claiming diminished capacity. In this article, I propose expanding categories of medical exemptions to consider mental health contexts, and accommodations be provided to those with diverging minds who are vaccine skeptic. I conclude with a clarion call to madvocates to stand against the violence of coercing vaccinations.